2022
DOI: 10.1073/pnas.2111228119
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides thetaiotaomicron uses a widespread extracellular DNase to promote bile-dependent biofilm formation

Abstract: Bacteroides thetaiotaomicron is a gut symbiont that inhabits the mucus layer and adheres to and metabolizes food particles, contributing to gut physiology and maturation. Although adhesion and biofilm formation could be key features for B. thetaiotaomicron stress resistance and gut colonization, little is known about the determinants of B. thetaiotaomicron biofilm formation. We previously showed that the B. thetaiotaomicron reference strain VPI-5482 is a poor in vitro biofilm former. Here, we demonstrated that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 63 publications
2
22
0
Order By: Relevance
“…2c; Supplementary Fig. S5e, g) that are both known to contribute to Bacteroides fitness under bile stress (Bechon et al, 2022; Liu et al, 2021). In case of the BT_2792 – BT_2795 operon that encodes a bile salt tolerance-conveying efflux pump (Liu et al, 2021), we observed a TSS and alternative start codon 60 nt downstream of the annotated one (red and black ‘ATG’ in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2c; Supplementary Fig. S5e, g) that are both known to contribute to Bacteroides fitness under bile stress (Bechon et al, 2022; Liu et al, 2021). In case of the BT_2792 – BT_2795 operon that encodes a bile salt tolerance-conveying efflux pump (Liu et al, 2021), we observed a TSS and alternative start codon 60 nt downstream of the annotated one (red and black ‘ATG’ in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…f, Gentamicin vs. TYG control. g, Venn diagrams display the overlap of bile salts-specific gene expression (significantly upregulated) between our dataset and that obtained in (Bechon et al, 2022). The associated heat map depicts highly upregulated operons including components of two efflux systems ( BT_2793-BT_2795 , BT_2685-BT_2689 ) as well as an outer membrane protein and a calcineurin superfamily phosphohydrolase ( BT_0691-BT_0692 ).…”
Section: Supplementary Figure S1mentioning
confidence: 88%
See 2 more Smart Citations
“…This alignment reinforces our contention that peanut supplementation can effectively act as a dietary adjunct, fostering the development of gut microbes that participate in the metabolism of food substrate. Furthermore, the escalation of Bacteroides thetaiotaomicron , a contributor to bile-dependent gut biofilm formation, 50 following 90 days of supplementation is noteworthy. This suggests a direct potential benefit to the host in terms of bolstering gut maturation.…”
Section: Discussionmentioning
confidence: 99%